Point-of-sale glass bottle recycling: indoor airborne exposures and symptoms among employees. Issue 7 (18th June 2004) - Kennedy, S M; Copes, R; Bartlett, K H; Brauer, M
Abstract : Aims: To assess the impact of newly introduced point-of-sale glass bottle recycling on indoor air quality and employee health. Methods: Airborne exposures and both chronic and acute respiratory and somatic symptoms were surveyed among 226 employees at 36 randomly selected liquor stores with bottle recycling and in-house glass breaking. Each store was visited twice; between visits glass breaking was discontinued for one month in half the stores (selected at random), although bottles were still collected and stored on site. Rates of chronic symptoms were compared to an external, unexposed control population. Results: Geometric mean exposure levels were 0.18 mg/m 3 for inhalable particulate matter and 3.6 EU/m 3 for endotoxin (270 personal samples); 1064 CFU/m 3 for viable fungi (648 area samples). Fungal levels were associated with visibly mouldy bottles being broken, outdoor fungal counts, and uncovered glass bins. Exposures were not altered by the intervention of shutting down glass breaking machinery. Compared to controls, employees reported more work related chronic chest tightness and chronic nasal symptoms. Acute chest symptoms were associated with breaking visibly mouldy bottles, but not with measured fungal counts. Inhalable particulate matter levels >0.2 mg/m 3 were associated with acute upper airway irritation. Somatic symptoms were associated with measures of psychosocial job strain. Conclusion: Results suggest that this type of recycling programme may generate fungal exposures sufficient to elicit upper airway and chest symptoms.